Foot over pronation problem among undergraduate students: a preliminary study - Nur Saibah Ghani,; Nasrul Anuar Abd Razak,; Juliana Usman,; Gholizadeh, H. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Over pronation is a dysfunctional movement where the foot has turned in excessively from its neutral line and can lead to misalignment of the foot and leg in humans. The purposes of this study are to investigate the ankle biomechanics behavior in individuals among the undergraduate students with over pronation foot and provide guidelines to help correct the foot deformities. 10 subjects with over pronated foot where volunteer but only 7 pass the selection test and divided into two group normal subjects (n=2) and over pronated subjects (n=5). Vicon motion analysis was used to observe and analyze the gait cycle and the ankle range of motion in individuals with over pronation. The study found that the ankle joint during the initial contact was below 5° for all subjects. Subject 2 shows the lowest ankle angle during initial contact while for mid stance phase, subject 3 shows the highest ankle angle which was 24.15° on left foot and 28.30° on right foot. From the ANOVA test, the p value for ankle joint angle was less than 0.05, which indicates that there was significant difference between all the subjects. The ankle angle depended on the muscle movement as the muscles and ligaments tried to stabilize and move the foot by controlling the angle to make sure the foot is in correct position and can move forward. As conclusion, there are significant differences for ankle behavior between normal and over pronated subjects, thus proper guideline for exercise or treatment can help to overcome this problem.